QUALITY FOOD RELATIONS AND ATMOSPHERE STORE OF CONSUMER PURCHASE DECISIONS - Rina Febriana; Luthfa Nurridha; Guspri Devi Artanti (LPPM, Universitas Negeri Jakarta, 2025)
Abstract: This study aims to determine and analyze the relationship between food quality and store atmosphere with consumer purchasing decisions. In this study used a sample of 98 respondents. Sampling using purposive sampling technique. The method of data analysis using simple and multiple regression analysis models, while to test the hypothesis using t-test and F test. This research use error level 0,05. The result of simple regression analysis shows there is the relationship between food quality to consumer purchase decision and there is the relationship between store atmosphere to consumer purchase decision. Meanwhile, the result of multiple regression analysis models shows the simultaneously variable quality of food and store atmosphere have a significant relation to consumer purchase decision variable with an obtained value of Fcount equal to 63,35 more significant than Ftabel = 3,09. Based on the calculation, the food quality is more dominant choose the relationship to consumer purchasing decision. Abstrak: Penelitian ini bertujuan untuk menentukan dan menganalisis hubungan antara kualitas makanan dan suasana toko dengan keputusan pembelian konsumen. Penelitian ini menggunakan sampel sebanyak 98 responden. Pengambilan sampel menggunakan teknik purposive sampling. Metode analisis data menggunakan model analisis regresi sederhana dan berganda, sedangkan untuk menguji hipotesis menggunakan uji-t dan uji-F. Penelitian ini menggunakan tingkat kesalahan 0,05. Hasil analisis regresi sederhana menunjukkan terdapat hubungan antara kualitas makanan dengan keputusan pembelian konsumen dan terdapat hubungan antara suasana toko dengan keputusan pembelian konsumen. Sementara itu, hasil model analisis regresi berganda menunjukkan bahwa variabel kualitas makanan dan suasana toko secara simultan memiliki hubungan yang signifikan dengan variabel keputusan pembelian konsumen dengan nilai F hitung sebesar 63,35 yang lebih signifikan daripada F tabel = 3,09. Berdasarkan perhitungan tersebut, kualitas makanan lebih dominan dalam memilih hubungan dengan keputusan pembelian konsumen.